PENGARUH BI RATE, INFLASI, NILAI TUKAR RUPIAH, DAN SERTIFIKAT BANK INDONESIA SYARIAH (SBIS) TERHADAP INDEKS SAHAM SYARIAH INDONESIA (ISSI) - Litriani, Erdah (I-Economics, 2017)
The capital market (capital market) is a market for various long-term financial instruments that can be traded, one stock. The capital market is a means of financing for companies and other institutions (eg government), and as a means for investment activities. Thus, the capital market facilitates various facilities and infrastructure of buying and selling activities and other related activities. There are several macroeconomic and monetary factors that can influence stock movement such as factor of BI Rate, Inflation, Rupiah Exchange Rate and Bank Indonesia Sharia Certificate (SBIS). The purpose of this research is to test and know the influence of BI Rate, Inflation, Rupiah Exchange Rate and Bank Indonesia Sharia Certificate (SBIS) Against Indonesia Sharia Index Shares Period June 2011 to May 2015. This research is quantitative research using secondary data collection method. This research uses five operational variables, namely BI Rate (X1), Inflation (X2), Rupiah Exchange Rate (X3), Bank Indonesia Sharia Certificate (X4) and Indonesia Sharia Shares Index (ISSI) (Y). The statistical test used in this study is a statistical-analysis model using quantitative analytical techniques, ie multiple linear regression. From the results of multiple linear regression shows that simultaneously the four independent variables significantly positively affect the Indonesian Sharia Stock Index (ISSI) (Y) and partially only the Rupiah Exchange (X3) which positively significant effect on the Temporary Sharia (ISSI) BI Rate (X1), Inflation (X2), and Certificates of Bank Indonesia Syariah (SBIS) (X4) did not show any effect on Indonesia Sharia Sharia Index (ISSI) (Y).